PEMANFAATAN SLUDGE KAWASAN INDUSTRI DENGAN MIKROORGANISME ASPERGILLUS NIGER, PSEUDOMONAS PUTTIDA DAN PENAMBAHAN AIR KELAPA MENJADI PUPUK ORGANIK - Febry Adam Pahlevi; Mohammad Mirwan (EnviroUS, 2021)
The use of sludge from wastewater treatment is very minimal and is not given much attention by many industries. PT SIER wastewater treatment sludge treatment by composting industrial sludge treatment so as not to pollute the environment. The composting method can be an alternative in waste management. The waste used is the sludge from PT SIER's sewage treatment along with vegetable waste. The study used a weight variation with a mixture rasio of 1:1, 2:1 and 1:2 with a total weight of 12 kg which was put into the bath with additional variations of mushroom, bacteria and coconut water. To each of the 12 reactor tanks with the addition of 3 reactor tanks without additional control. with a composting time for 20 days. The results of composting can reduce the C/N rasio and increase the macro nutrients which have met the quality standards of permentan NO. 70/Permentan /SR.140/10/2011. There is a reactor tank that is able to meet the quality standards with a C / N rasio of 16.58 and macro nutrient content of 4.3%.